Laterally positioned external carotid arteries: Two cadaveric case reports - Kara Coffman-Rea; Skylar Arwood; Karen E. Samonds; Dylan J. Fuchs; Julia P. Negrin (Translational Research in Anatomy)
Anatomical variations in the carotid vasculature are clinically significant due to their implications for various surgical procedures and their potential to produce a range of symptoms. This case report highlights two notable variations observed during routine cadaveric dissections. In both cases, the external carotid artery was positioned laterally. Both cases presented the superior thyroid artery and superior laryngeal artery branching at the level of the carotid bifurcation; one case showed both arteries originating directly from the bifurcation, while the other case exhibited the typical branching pattern where the superior laryngeal artery branches from the superior thyroid artery. One case also included a high carotid bifurcation above the typical location at the superior border of the thyroid cartilage.